Lymph vessels visualization from optical coherence tomography data using depth‐resolved attenuation coefficient calculation. Issue 9 (17th June 2021) - Moiseev, Alexander A.; Sirotkina, Marina A.; Potapov, Arseny L.; Matveev, Lev A.; Vagapova, Nailya N.; Kuznetsova, Irina A.; Gladkova, Natalia D.
Abstract: Multimodal optical coherent tomography grows popularity with researchers and clinicians over the past decade. One of the modalities is lymphangiography, which allows visualization of the lymphatic vessel networks within optical coherence tomography (OCT) imaging volume. In the present study, it is shown that lymphatic vessel visualization obtained from the depth‐resolved attenuation coefficient distributions, corrected for the noise, shows improved contrast and detail in comparison with previously proposed approaches. We also argue that the two most popular approaches for lymphatic vessel visualization, namely simple intensity thresholding and vesselness calculation based on local Hessian matrix eigenvalues, imply different definitions of the lymphatic vessel's appearance in the OCT volume and lead to the different networks. Abstract : Multimodal Optical Coherent Tomography grows popularity with researchers and clinicians over the past decade. One of the modalities is lymphangiography, which allows visualization of the lymphatic vessel networks within OCT imaging volume. In the present study, it is shown that lymphatic vessel visualization obtained from the depth‐resolved attenuation coefficient distributions, corrected for the noise, shows improved contrast and detail in comparison with previously proposed approaches. We also argue that the two most popular approaches for lymphatic vessel visualization, namely simple intensity thresholding and vesselness calculation based on local Hessian matrix eigenvalues, imply different definitions of the lymphatic vessel's appearance in the OCT volume and lead to the different networks.